Execution of Students’ Plans in Mathematical Problems Solving - Wahyuni, Sela; Dahlan, Jarnawi Afgani (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Problem solving is one of the skills students need to implement and elaborate mathematical concepts in building other high-level thinking skills. Problem solving skills can be developed through practicing mathematical problem solving in a way or solving more than one. In solving problems, appropriate strategies or steps are needed, which are combining concepts, as well as principles that have been learned in advance by students. The purpose of this study was to determine the students' skills in executing mathematical problem-solving plans. This study uses a qualitative approach, then the data findings are analyzed descriptively. Data were collected from 4 grade 11 students of state high schools in Jatinangor, West Java. Students are given math problems and focus group interviews are conducted. The results showed that, student work in executing problem solving plans tended to lack a lot of mathematical skills. These skills include ignoring the basic concepts and principles of calculation as well as reading the available information. In other words, students' skills in solving mathematical problems fall into the poor category. This can be caused by several factors such as inaccurate, forgetfulness, haste, surrender, and anxiety. Based on these results, it is seen that the need to design classroom learning activities that can optimize the components of students' mathematical problem-solving skills so that they can grow and develop properly